Modelagem termodinâmica e análises paramétricas em processos de destilação com oscilação da pressão - Martins, Tássio Max dos Anjos (2023)
This work aims to study the pressure swing distillation (PSD) of binary azeotropic mixtures. The investigated binary mixtures were: chloroform-methanol, acetone-chloroform, THFmethanol, acetone-methanol and ethyl acetate-ethanol. First, the influence of the thermodynamic modeling of the vapor phase was studied, considering that high pressures are necessary in the process. The motivation for this investigation is based on the fact that several articles in the literature consider the ideal vapor phase. Thus, simulations and comparisons were performed based on the modified Raoult's law (ideal vapor phase) and the − formulation (Peng-Robinson and Hayden-O'Connell vapor phase), using the simulation software COCO/ChemSep, version 3.4. The second part of the work, considering the mixture chloroform-methanol, evaluated the effect of some operational parameters little explored in the literature through parametric analyses. These parameters were the selection of distillation column pressure, feed temperature and feed compositions. The results of the first part show that it is essential to consider the non-ideality of the vapor phase for a precise description of the phenomenon, since the different models alter the phase equilibrium of the mixtures. About the parametric analyses, the second part of the work, it was evidenced that the pressure selection reduces the energy costs of the reboiler by 10.89% and operating under vacuum is a viable proposal. The column feed temperature was studied between the range of 290 K and 340 K, having an optimized value at the temperature of 321.1 K. The feed molar composition equal to 0.4 of chloroform showed a reduction in the reboiler service of 11.7%. The mentioned effects originate from the mathematical modeling of the mass balance of the process. Considering the base case of the chloroform-methanol mixture, the parametric analyzes reduced the total heat of the reboilers and the TAC by approximately 21.3% and 17.6%, respectively.